2012
DOI: 10.5535/arm.2012.36.5.665
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Extracorporeal Shock Wave Therapy on Myofascial Pain Syndrome

Abstract: ObjectiveTo investigate the effect of extracorporeal shock wave therapy (ESWT) on myofascial pain syndrome (MPS).MethodThirty patients with MPS in trapezius muscle were randomly divided into two groups, ESWT group (n=15), and trigger point injections (TPI)+transcutaneous electrical nerve stimulation (TENS) group (n=15). For a total of 3 weeks, ESWT was undertaken with 1,500 pulse each time at one week interval totaling 4,500 pulse, TPI for once a week totaling three times and TENS for five times a week totalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
75
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 19 publications
8
75
0
2
Order By: Relevance
“…In spastic muscles of patients affected by brain lesion, ESWT reduces muscle tone in the short term 1213. In myofascial pain syndrome, ESWT significantly reduces muscle pain immediately after treatments 11. These results support a direct effect of ESWT on muscles.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In spastic muscles of patients affected by brain lesion, ESWT reduces muscle tone in the short term 1213. In myofascial pain syndrome, ESWT significantly reduces muscle pain immediately after treatments 11. These results support a direct effect of ESWT on muscles.…”
Section: Discussionmentioning
confidence: 63%
“…Clinically, hamstring muscle tightness is commonly measured indirectly by these two methods. These tests are easy to perform and are reliable 891011. The study design is illustrated in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…[10][11][12][13] ESWT improves blood circulation in capillaries, and it reduces the tension and stiffness of muscles, which can interfere with blood flow and cause excessive stimulation of nociceptors and nerves. 14) According to…”
Section: Discussionmentioning
confidence: 99%
“…Most research in shockwave therapy has focused on understanding the mechanism which results in the establishment of a mechano-sensitive feedback loop between the acoustic impulse and the stimulated cells, and involves specific transduction pathways and gene expression. Taking as valid the Energy Crisis Hypothesis, and considering the mechano-transduction effect of ESWT in other diseases [9][10][11][12][13][14][24][25][26][27][28][29] it could be posited that ESWT in MPS may increase perfusion, promote angiogenesis and alter the pain signaling in ischemic tissues caused by the influx of calcium. On the other hand, recent articles have demonstrated that free nerve endings degenerate after the application of ESWT, and that ESWT produces a transient dysfunction of nerve excitability at the neuromuscular junction, [9][10][11][12][13][14][24][25][26][27][28][29] by bringing about the degeneration of AChR.…”
Section: -14mentioning
confidence: 99%
“…[9][10][11][12][13][14][24][25][26][27][28][29] There are evidences of the efficacy of Extracorporeal Shockwave Treatment on Myofascial Pain Syndrome as in the Table 1. Müller-Ehrenberget et al 24 revealed the efficacy of focused ESWT on MPS (Piezoelectric device: Piezo Son100) for alleviating pain in 95% of the 30 patients at 3 months, (800 impulses of energy level:0.04-0.26 mJ/mm2;6 Hz; average 7 treatments, 2 sessions per week) 24 Jeon et al 25 demonstrated that 3 sessions of 1500 pulses of low energy (0.10 mJ/ mm2 ) with focused ESWT (Electrohydraulic: Evotron RFL0300) weekly is as effective as TENS and TP injection on 30 patients with MPS in trapezius muscle, measuring the results in terms of pain (visual analog scale e VAS e and McGill Pain Questionnaire), as well as on the Roles and Maudsley scale. 25 Ji et al 26 used an electromagnetic device (Dornier AR2) on MPS of upper Trapezius compared to placebo.…”
Section: -14mentioning
confidence: 99%